Efikasi Diri dan Implikasinya terhadap Hasil Belajar Siswa dalam Konteks Implementasi Kurikulum SMK Nasional Malang - Yayi Febdia Pradani; Rangga Abi Praya; Prasasti Pambayun Anjarwati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to determine the effect of self-efficacy on learning outcomes of vocational high school students in the context of implementing a competency-based curriculum. The approach used is quantitative with an ex post facto method. The study population was grade XI students of SMK Nasional Malang, with a total sample of 92 students taken (saturated sampling). Self-efficacy data were obtained through a questionnaire using a Likert scale, while learning outcome data were obtained from mid-semester report card scores. The results of the linear regression test showed that the data were normally distributed and had a linear relationship. The t-test showed that self-efficacy had a significant effect on student learning outcomes (p < 0.05). These findings confirm that self-efficacy is an important indicator in supporting the achievement of learning outcomes, especially in vocational education that demands students' independence, responsibility, and readiness to face the challenges of practice-based learning. Students with high self-efficacy tend to have better learning motivation, are able to manage learning strategies effectively, and demonstrate a high level of independence in completing assignments. Therefore, learning development in vocational high schools should not only emphasize technical aspects, but also need to strengthen students' self-confidence in achieving learning success.